New Biological Insights Into How Deforestation in Amazonia Affects Soil Microbial Communities Using Metagenomics and Metagenome-Assembled Genomes - Kroeger, Marie E.; Delmont, Tom O.; Eren, A. M.; Meyer, Kyle M.; Guo, Jiarong; Khan, Kiran; Rodrigues, Jorge L. M.; Bohannan, Brendan J. M.; Tringe, Susannah G.; Borges, Clovis D.; Tiedje, James M.; Tsai, Siu M.; et al. (Frontiers in Microbiology, 2018)
Deforestation in the Brazilian Amazon occurs at an alarming rate, which has broad effects on global greenhouse gas emissions, carbon storage, and biogeochemical cycles. In this study soil metagenomes and metagenome-assembled genomes were analyzed for alterations to microbial community composition, functional groups, and putative physiology as it related to land-use change and tropical soil. A total of 28 metagenome-assembled genomes were assembled encompassing 10 phyla, including both dominant and rare biosphere lineages. Amazon Acidobacteria subdivision 3, Melainabacteria, Microgenomates, and Parcubacteria were found exclusively in pasture soil samples, while Candidatus Rokubacteria was predominant in the adjacent rainforest soil. These shifts in relative abundance between land-use types were supported by the different putative physiologies and life strategies employed by the taxa. This research provides unique biological insights into candidate phyla in tropical soil and how deforestation may impact the carbon cycle and affect climate change.